Revolutionizing K-12 blended learning through the i2Flex classroom model - Avgerinou, Maria D., 1966-; Gialamas, Stefanos P.; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book presents a well-rounded discussion on the i2Flex model, highlighting methods for K-12 course design, delivery, and evaluation in addition to teacher performance assessment in a blended i2Flex environment"--Provided by publisher.
The i2Flex instructional methodology implemented in middle school classes for young EFL and foreign language learners / Jenny Eugenia Grigoropoulos, Heike Arnold -- Hooked on mathematics / Dora Andrikopoulos, Matina Katsiyianni -- Towards a model of playful learning: gamification strategies in the i2Flex classroom / Raphael Raphael -- Flipping and flexing in science: video lessons and the i2Flex model / Labrini Rontogiannis -- Creativity in interdisciplinary teaching: how we used i2Flex in a co-teaching framework / Caitlin R. Lewis, Margarita Gournaris -- "Reverse engineering" of IB history exemplars: applying the i2Flex methodology to improve students' analytical writing / David I. Nelson -- Fitness revisited: mobile learning in physical education / Angelos Dimitropoulos -- i2Flex and the community of inquiry framework: how their blend transformed my IB French class / Antonia Fyrigou -- Implementing virtual lab learning to high school / Evangelia Prodromidi -- The humanities program: an innovative classic / Kathleen Jasonides, Janet Karvouniaris, Amalia Zavacopoulou -- Entering the i-world of teens: An ACS Athens advisory model for college applications / Mandy Dragatakis, Anna Makris, Peggy Pelonis -- The effects of i2Flex learning on students' holistic well-being and academic success / Alessandra Sax.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 07/07/2016).
Keywords: Learning, Psychology of; Blended learning; Student-centered learning; Schools, American -- Greece -- Athens; Action research in the blended classroom; Best teaching practices; Blended teaching; Educational technology; Faculty development; Flipped classroom model; Information design; Instructional design; Teacher assessment; Web-based learning; Electronic books